New prospects for the management of cardiovascular effects of tyrosine kinase inhibitors in patients with chronic myeloid leukemia - Almeida, Ana G. (2019)
© 2018 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CC-BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).